Optimization of Pollen Germination in Tectona grandis (Teak) for Breeding Programs - Hine, Ana (2019)
Teak has become one of the most widely planted species in tropical regions of the world, given its high price for its timber in international markets. This has motivated the development of tree improvement programs in the Latin American region and in the tropical world in general. The latest advances have achieved clonal forestry at an operational scale. Recently, important efforts are being made to advance towards the next breeding generation, since knowledge about floral biology and pollen management have become important issues. A breeding program is being developed through the Tree Improvement Cooperative GENFORES—a vinculation model between the academy and forestry companies that was initiated in Costa Rica and now involves six Latin American countries. In order to advance into the next breeding generations, building capacities in topics such as pollen banks requires pollen quality, thus enabling the exchange of pollen among cooperative members. Pollen fertility studies are of considerable value in breeding programs, in order to determine pollen viability and germination in collections of genotypes, before going into mating operational activities. In this study, we optimized pollen quality analysis protocols in terms of the viability and germination of fresh teak pollen. Results of this research show that 90% viability and 28% germination can be achieved in fresh pollen grains, both inside and outside the anther, previously dehydrated in silica gel for 2 to 4 h (40% and 33% humidity, respectively). Brewbacker and Kwack (BK) medium at 10% of its salts + 10% sucrose and at a pH of 7 must be used as the germination medium. It is possible to evaluate teak pollen quality using the parameters defined in this study, which will in turn allow pollen management and purification, providing an opportunity for carrying out controlled crosses at an operational scale as part of teak breeding programs.